Effectiveness of CoronaVac primary series with and without booster against hospitalized COVID-19 during the Omicron-predominant epidemic wave in the Philippines: a test-negative case–control study - Kristal An Agrupis; Michelle Ylade; Yang Yang Qi; Maria Vinna Crisostomo; Jedas Veronica Daag; Gianne Lariz Magsakay; Jude Raphael Lo; Kiarah Louise Florendo; March Helena Jane Lopez; Jayne Marie Enriquez; Irish Lobitaña; Gretchen Bonita Ranada; et al. (Expert Review of Vaccines)
Background CoronaVac (Sinovac) was initially effective against symptomatic COVID-19 and severe outcomes, but its performance against the immune-evasive Omicron variant remains uncertain. This study evaluated the effectiveness of CoronaVac against hospitalized COVID-19 among Filipino adults during the Omicron-dominant wave.Research design and methods We conducted a test-negative case–control study from November 2022 to November 2023 in three tertiary government hospitals in the Philippines. Adults hospitalized with acute respiratory illness (ARI) were enrolled. Cases tested positive for SARS-CoV-2 by RT-PCR; controls tested negative. Vaccination status was confirmed via vaccination cards or the national registry. Conditional logistic regression estimated vaccine effectiveness (VE). Genomic sequencing identified circulating variants.Results Among 2,365 participants, 165 (7.0%) were COVID-19 positive. In an age-matched analysis (104 cases, 408 controls), two CoronaVac doses provided 61.3% protection (95% CI: 5.3–84.2%) against critical illness. A heterologous booster conferred 65.9% protection against severe disease, 90.1% against critical illness, and 60.5% against death. Sequencing of 23/46 samples confirmed Omicron XBB-like variants.Conclusion Two doses of CoronaVac offered moderate protection against severe COVID-19. Heterologous boosters significantly improved protection, especially against critical illness and death, supporting ongoing booster campaigns after inactivated vaccine priming.